Hybrid Learning:A Paradigm Shift - Sharaj, A. P.; Pattankar, Rohan; Rajeev Lochan, P.; Murthy, Madhav (Journal of Engineering Education Transformations, 2025)
The paper discusses the views of the students regarding different Hybrid Learning methods and the awareness of students regarding these methods. The paper also elucidates on the different factors influencing the motivation of students to attend lectures. An online survey was conducted on 300 students across 30 different colleges, majority of them being autonomous thus, having a variety of curriculum standards and assessment techniques, to collect information necessary to deduce conclusions regarding the above mentioned. The study indicates that the awareness of MOOCs, Outcome Based Education and Social learning is high among students though the level up-to which they’re aware is limited. But the study shows that majority (i.e., around 88%) of students are unaware of the concepts like Flipped Classroom, Blended Learning and the use of Virtual Reality as a part of their curriculum. The study clearly shows that the one of the main reasons for motivation of students to attend classes are the teachers’ content delivery and academic requirements. So, by making use of technology, self - learning methods and project activities in the curriculum and by providing training to teachers, interest in students to learn a course can be increased significantly and even ensuring a higher quality of content delivery by the course instructors.